PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN VIDEO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI BARISAN DAN DERET ARITMATIKA DI KELAS XI A SMK MUHAMMADIYAH SIGI: Application Of The Video Assisted TGT Times Games Tournament Type Cooperative Learning Outcomes In Arithmetic Sequence and Series Material In Class XI A Of Muhammadiyah Sigi Vocational School - Meliasari, Cindy; Pathuddin; M, Bakri (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
Research aim is obtain description the implementation of the learning model tipe teams games tournament (TGT) to improve learning outcomes student’s on the materials sequences and progression of arithmetic in class XI A SMK Muhammadiyah Sigi. The research is research class action referring to design research by Kemmis and Mc. Taggart that is planning, action, observation dan reflection. The subject of this study were 20 students of class XI A at Muhammadiyah Sigi Vocational High School who were registered in the 2019/2020 who were 20 students. From the subject of research that selected three students as informants. This research was conducted in two cycles. Based on the results of the final action test, the percentage of student’classical learning completeness in the first cycle was 60% and the percentage of student’classical learning completeness in the second cycle was 85%. For the results of observations of teacher and student activities in the first cycle were in the good category and the second cycle was in the very good category. The result showed that the implementation of learning model cooperative type TGT can improve learning outcomes student’s on the materials sequences and progression of arithmetic in class XI A SMK Muhammadiyah Sigi, with levels are: 1) presentation of class, 2) Teams, 3) game, 4) Tournaments, and 5) awards of group.